Reassessing the Role of Culture in Achieving the Sustainable Development Goals (SDGs): The Nigerian Narrative - Celestina Ekene Chukwudi; Grace Ugochi Isaac (Universitas Medan Area, 2026)
Nigeria’s extensive cultural diversity, spanning over 250 ethnic groups, and its expanding creative economy hold significant potential for advancing sustainable development. However, the underutilization of cultural assets in national development strategies represents a persistent challenge. This study investigates how culture contributes to sustainability in Nigeria and evaluates the extent to which government policies, particularly the 1988 National Cultural Policy, align with the United Nations Sustainable Development Goals. Adopting a qualitative research design, the study analyses policy documents, government reports, and academic literature using thematic and content analyses, guided by the Cultural Heritage and Creativity Framework. Findings reveal that culture has been deployed in sustainability efforts through arts, music, media campaigns, and creative industries to promote civic education, peace-building, and environmental awareness. Despite this progress, weak policy implementation, funding limitations, and exclusion of cultural stakeholders constrain impact. The study concludes that systematic integration of cultural heritage and creativity into development planning, education, and SDG monitoring is crucial to strengthening Nigeria’s sustainability agenda and providing a replicable model for other African states.